Toward bridging disciplinary divides: a peer-education perspective on enhancing university belonging - Galioto, Marina (Frontiers in Education, 2025)
Since a sense of belonging at university is conducive to the feeling of being recognized as a member of a specific group sharing common thoughts and values within that environment, it is foundational for educational practitioners to explore how this sentiment can be enhanced for community improvement. In academia, peer interactions and collaborative settings can also produce positive effects, contributing to increased interdisciplinary collaboration and intellectual outcomes. In this framework, the higher education landscape provides great research potential to explore the importance of a sense of belonging due to its cooperative system and likelihood of people cohabiting (classrooms, cafeteria, for example). The scenario is also enriched by the possibility of discovering trends for future challenges. This research design aims to find patterns in university students’ sense of belonging among different fields of study, exploring similar or dissimilar attitudes across social networks. Researchers are promoting an alternative approach for educational environments to enhance the sense of belonging among students at university.